Omental Infarction with Acute Appendicitis in an Overweight Young Female: A Rare Presentation - Vishnu R. Mani; Shantanu Razdan; Tonny Orach; Aleksandr Kalabin; Rinil Patel; Ali Elsaadi; Kiyoe Sullivan; Federico Gattorno (Case Reports in Surgery)
Omental infarction is an uncommon cause of acute abdomen but one that clinically mimics more serious and common causes of acute abdomen like appendicitis and cholecystitis. Historically, it was diagnosed only intraoperatively during surgery for presumed appendicitis or other causes of acute abdomen. But with the increase in the use of imaging, especially abdominal computed tomography (CT) scan in the work-up for acute abdomen, more cases of omental infarction are being diagnosed preoperatively. This has also led to the observation that omental infarction is a self-limiting condition which can be managed conservatively. Currently, conservative management and surgery are the only treatment options for omental infarction with no consensus as to the best treatment modality. Having a patient with both acute appendicitis and omental infarction simultaneously is extremely rare with only two reported cases in the literature thus far. Here, we present a 10-year-old obese female who presented to our hospital with acute abdomen and was found to have acute appendicitis and omental infarction. The patient underwent laparoscopic appendectomy and resection of the infarcted omentum and had uneventful recovery and was discharged on the second postoperative day. In this report, we present a review of current literature on omental infarction and highlight the importance of imaging especially abdominal CT scan in the nonoperative diagnosis and treatment of omental infarction.